Increasing Crop Profitability through Adoption of Ridge Planting of Rice Crop in Punjab, and Wheat & Banana Crops in Sindh Province of Pakistan: Ridge Planting of Rice, Wheat & Banana Crops in Pakistan - Hussain, Abid; Khathian, Mohsin Ali; Ullah, Sami; Ullah, Saad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Ridge sowing of crops has clear advantages over traditional irrigation practices; specifically reduces use of water and other inputs, helps better crop management, and delivers higher crop productivity. The study analyses adoption and cost-benefit of ridge planting of rice crop in mixed cropping zone of Punjab, and wheat and banana crops in mixed cropping zone of Sindh province of Pakistan. It is based on primary data collected from 120 adopter farmers of the technology, including 40 farmers each planting rice crop on ridges in central Punjab (Toba Tek Singh district), sowing wheat crop on ridges in central Sindh (Shaheed Benezirabad district) and planting banana crop on ridges in lower Sindh (Tando Allahyar district) during crop season 2017-18. Field surveys for the study were conducted in March to May, 2018. It is found that adoption of the technology results into increase in land preparation cost of rice, wheat and banana crops by about 13, 2 (excluding cost of ridge sowing through drill) and 47 percent, respectively. Adoption of the method resulted into productivities of rice, wheat and banana crops of 56.5, 48.9 and 666.4 mound per acre, respectively. Though, productivities of wheat and banana crops were higher than traditional sowing practices of the crops by about 22 and 20 percent, respectively. While that of rice crop was less than conventional flat sowing method by three percent. Adoption of ridge sowing method resulted in decrease in irrigation cost by 25, 36 and 40 percent in rice, wheat and banana crops, respectively. The method resulted in decrease in total cost of production of rice and wheat crop by about two and seven percent, respectively; while, increase in that of banana crop by four percent. Benefit cost ratios of the technology for rice, wheat and banana crops are 1.03, 1.41 and 2.26, respectively; against 1.04, 1.08 and1.97 obtained through traditional flat sown/ flood irrigation of crops, respectively. Thus adoption of the technology is beneficial in case of wheat and banana crop, but at par in financial gains with conventional sowing in case of rice crop.